ULIN BARONG SEKELOA AS AN INTANGIBLE CULTURE OF BANDUNG - Mila Mardotillah; Anwari Masatip; Arief Syaifudin (Politeknik Pariwisata NHI Bandung, 2024)
Ulin Barong Sekeloa is one of art culture were born from the local community in Bandung has been designated as an intangible cultural heritage of West Java Province from Bandung City. The meaning of Ulin is to play, Sirah Barong is the head of the barong, and Sekeloa is the name of a place in Bandung. This attraction is accompanied by traditional Sundanese musical instruments with an accompaniment of 12 peoples. Ulin Barong Sekeloa has appeared since 1885, the pioneer figure was Muhamad Tharwi and the development was carried out by Atjeng Sulaeman who is a living figure of Ulin Barong Sekeloa. The aim of the research is to describe the Ulin Barong Sekeloa for the preservation of traditional art culture and the potential for quality Bandung City cultural tourism attractions, especially for improving the economy of artists after the Covid-19 pandemic. The method used is descriptive analytic by exploring the potential of the Ulin Barong Sekeloa attraction to become a Cultural Tourism Attraction in Bandung City. The results show that the community empowerment ecosystem has made Ulin Barong Sekeloa one of the Intangible Cultural Heritage of Bandung city still exists until today which has the potential to become a cultural tourism attraction which can become a quality cultural destination in Bandung City. The conclusion obtained is that the existence of Ulin Barong Sekeloa until now has been formed from the results of the adaptation of society to changing times as the spearhead of the conservation of Ulin Barong Sekeloa.